KONTRIBUSI ISLAMIC BANKING FINANCING AND VARIABLES MACRO ECONOMIC TERHADAP TINGKAT KEMISKINAN DI INDONESIA - Riky Soleman (Izdihar: Jurnal Ekonomi Syariah, 2024)
Poverty is a global issue faced by many countries in the world, including Indonesia. The purpose of this study is to examine the level of poverty in Indonesia by measuring the financing of Islamic banking, education, health, TPAK and inflation against the level of poverty in Indonesia. The data source used is panel data obtained from the Central Bureau of Statistics (BPS) for the 2010-2020 period. Data analysis used panel data regression with Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM) Approach processed with E-Views 10. The results of this study indicate that the estimated model chosen in this study is Fixed The Effect Model shows the results of the Islamic Banking Financing, RLS, UHH, TPAK and Inflation variables that have a significant effect in a negative direction on the level of poverty for the RLS variable that has a simultaneous effect on the mission level while UHH has a significant effect in a negative direction. This means that if there are independent variables simultaneously, then the level of poverty in Indonesia is increasingly leading to change. Whereas in the simultaneous test the prob value of the F-Statistic is 0.000000 <0.05, which means that the five independent variables simultaneously influence the level of poverty in Indonesia. And the Adjusted R-Square value is 0.987540 which means that 90% of the Islamic Banking Financing, RLS, UHH, TPAK and Inflation variables in this study are able to explain the poverty rate variable in Indonesia. While the remaining 10% is explained by other variables outside the model.